Śilpī mānusha Yāminī Rāẏa - Samanta, Rabindra Nath; Caṭṭopādhyāẏa, Sumanā; Māji, Rabīndranātha (Pustaka Bipaṇi, 1980)
Collection of articles, press reportage, reminiscences of associates, letters, etc. on the life and work of the Bengali painter Jamini Roy, 1887-1972.